(untitled) (Economia Aplicada, 2004)
During the nineties some economists expected that the intense process of productive internationalization of the Brazilian economy would bring gains, particularly regarding to the trade performance of the country. This paper aims at evaluating the importance of the ownership - foreign or national as a determinant of trade of the industrial firms in Brazil between 1996 and 2000. The analysis used individual information about more than 50.000 industrial companies in the period into a panel data econometric model. The results show that transnational corporations seem to be more integrated into international trade than locally owned firms. However, this larger integration takes the form, essentially, of stronger import activities more than of larger exports. These results contradict the expectations of some economists: that foreign companies could collaborate for a better Brazilian trade performance during the period.